Arab Spring : the incomplete revolution / Mahdi Salih Hammoodi Al Sammarraie - Hammoodi Al Sammarraie, Mahdi Salih (Universiti Teknologi MARA, Shah Alam, 2012)
Theoretical bases of democracy exist in the constitutions and laws of many Arab states. Human Rights, public liberties, freedoms of assembly or forming political parties, Non-Governmental Organizations (NGOs) and trade unions, are usually mentioned in the texts. But, the application is far away from democracy. The absence of democracy is only one face of the complex crisis in Arab countries. In fact, the entire system is outdated. It needs to be changed or at least reformed to harmonize the cadence of development in the world. Worried about their future and the destiny of their people, Arab youths have revolted in many countries simultaneously. Changing to democratic and developed society is their main shared objective. The common name used to describe this revolt is "Arab Spring". This article tries to explain the reasons and motivations of this new phenomenon. It will look at the achievements of the revolutions that took place and examine their internal, regional and international implications.